Bài phát biểu của các đại biểu Quốc hội về Chương II của Hiến pháp tại phiên họp 27/3/1992 - Chu Hạp (1992)
Nội dung Bài phát biểu của các đại biểu Quốc hội về Chương II của Hiến pháp tại phiên họp 27/3/1992.